LIVE STREAMING INFLUENCER AND PRODUCT CONTENT AS DETERMINANTS OF PURCHASE INTEREST SHOPEE CONSUMERS IN TASIMALAYA CITY - Nurna Yuni; Hary Firmansyah; Depy Muhamad Pauzy (Jurnal Manajemen Sains dan Organisasi, 2024)
Objective – The aim of this research was to determine the influence of Live Streaming Influencers and Product Content on Customer Buying Interest toward Shopee Consumers in Tasikmalaya City.Design/Methodology/Approach – This quantitative research was aimed at an online survey of 127 respondents who used Shopee accounts for online shopping. Sample data was collected through purposive sampling and analyzed using Multiple Linear Regression via SPSS.Findings – The research outcome show that Live Streaming Influencers have no effect on Customer Buying Interest. Meanwhile, Content of Product has a significant effect on Customer Buying Interest. Then Live Streaming Influencers and Content Of Product together have a significant influence on Customer Buying Interest.Conclusion and Implications – The findings of this research indicate that Live Streaming carried out by Influencers did not necessarily a guarantee for attracting buyers who have certain intentions about the products they want. Then by diverse and interesting product content, consumers gain literacy according to their needs for product information. Keywords: Live Streaming Influencer, Content Of Product, and Customer Buying Interest